A study on characteristics of flow field around vehicle body. Issue 1 (June 2021) - Zhao, Ruochen; Liu, Zhen; Liu, Yinzhen; Luo, Xiaobo; Sun, Yanan
Abstract: A numerical simulation calculation is performed using large eddy simulation method to investigate the characteristics of flow field around vehicle body, analyze the change rules of the velocity and pressure of the three-dimensional flow field around the vehicle body, as well as the frequency domain characteristics of the aerodynamic coefficients in the vehicle body. The results reveal that with the gradually expanding distance from the rear of the vehicle body, the velocity in the flow field around the vehicle body gradually recovers and reaches the incoming flow velocity at 0.9m from the rear of the vehicle body. Within the range of 0∼50HZ, the resistance coefficient and lift coefficient undergo a peak attenuation to about 20%, with a fluctuation of aerodynamic coefficient mainly within the range of 0∼500HZ. The research results are of certain significance and value for analyzing and applying the characteristics of flow field around vehicle body.